The Role of Epigenetic Alterations Involved in Sepsis: An Overview - Hassan, Fatima I.; Didari, Tina; Khan, Fazlullah; Mojtahedzadeh, Mojtaba; Abdollahi, Mohammad (Current Pharmaceutical Design, 2018)
Background: Sepsis is among the leading causes of death with no specific etiology or treatment. Increase in health burden in terms of cost, morbidity, and mortality is the reason behind the continuous search for different treatment modalities which involve several targets/approach and one of them includes the involvement of epigenetics in sepsis. Objective: This review was carried out to explain the epigenetic alterations involved in sepsis, as it affects the disease progression, diagnosis, and treatment. Methods: Information used in this review was obtained from different databases including PUBMED, SCOPUS, Web of Science, and EMBASE. Keywords were used as search terms. Result: In this review, we provided a concise overview of the significant role of epigenetic alterations in sepsis pathophysiology as it relates to disease progression, diagnosis and treatment derived from in vitro, in vivo, and human studies. These mechanisms affected various targets and pathways involved in sepsis modulation, which correlates with morbidity and mortality. Change in DNA methylation pattern, histone modification, and microRNA regulation has been shown in sepsis models to silence or activate pro-inflammatory genes such as TNF-α and interleukins, anti-oxidant enzymes, and many signaling pathways. Drugs that target these pathways have proven effective in sepsis treatment. Conclusion: Epigenetic processes involve specific enzymes detected in the blood and other body fluids which can potentially serve as diagnostic, therapeutic, as well as prognostic tools in sepsis. Epigenetic mechanisms can provide a highly sensitive and accurate method for sepsis diagnosis using blood and other body fluids.
Keywords: treatment